Explosive eruption, flank collapse and megatsunami at Tenerife ca. 170 ka - Raphaël Paris (Nature Portfolio, 2017)
Oceanic shield volcanoes flank failures can generate large tsunamis. Here, the authors provide evidence that two tsunamis impacted the coast of Tenerife 170 Ma, the first generated by volcano flank failure and the second following a debris avalanche of the edifice during an on-going ignimbrite-forming eruption.